(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This work emerges as a result of our feminist activism and outreach research developed with a group of women in the Ciudad Obispo Angelelli II neighborhood, south of Cordoba city, Argentina. The group, made up of women between 20 and 60 years of age, is organized around a community kitchen, which has served as a space for critical reflection, with the aim of creating possible worlds, centered on the concept of Good Living. The meetings, held biweekly, are structured as workshops or feminist circles. The work is framed in the contributions of Latin American feminisms, which promote the idea of creating community as a path towards the depatriarchalization of life. In this article, we share reflections arising from two axes of collective work: a food workshop and a dance and self-support workshop. We defend a critical, feminist and militant outreach practice, which questions the traditional postulates of neutral, objective and apolitical knowledge.